Tafsir Al-Qur’an Tematik tentang Manajemen Mutu Kaderisasi Ulama di Pondok Pesantren - Mukaffan Mukaffan (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2020)
Abstract This article examines thematic Al-Qur'an interpretations about the quality management of regeneration ulama in Islamic boarding schools. From the results of the analysis of the study of the verses of the Qur'an, it can be concluded that the implementation of quality management of regeneration must have values: 1) quality management must be oriented to the quality of cadres. 2), quality management must have a different value (distinction). This also applies to goods or services. 3), quality management must be oriented to the needs of the community in the present and the future. In creating products and services, besides services must be in accordance with the needs of the community, the products or services offered must be in accordance with the needs of the community in the future. Keywords : Quality Management, Regeneration, Ulama,